H* Transformasi Citra Digital Untuk Mendapatkan Kompresi Optimal Dengan Metode Lossless - Hastha Sunardi; Zulkifli (Teknomatika, 2020)
Previous topics of compression research have largely focused on compressions of compression methodes in terms of compression ratios. This research provides the need for a stage before compression, namely the need for a transformation process of the test image to obtain aminimum file size before compression, so that when compressed it will produce the minimum file size, which in this study is called optimal compression. The test image referred to in this research are two images that have different color structures and shapes, which are distinguished in regular and irregular images. The results showed that by transforming the test image through rotation, the compressed image size was 5,8682 kB, while without transformation it was 6,1553 kB for regular images, with a rotation of 90 degrees. Meanwhile for irregular images with a 180 degree rotation, the compressed file size is 5,2236 kB, while without transformation it is 5,419 kB.